FAKTOR – FAKTOR YANG MEMENGARUHI USIA MENOPAUSE DI KELURAHAN BULURAN KENALI KOTA JAMBI TAHUN 2015 - Diniyati Diniyati; Neny Heriyani (Universitas Batanghari Jambi, 2016)
Every woman will be menopause, menopause when there will be changes in the body such as vasomotor symptoms are due to an imbalance between estrogen and progesterone that would interfere with the psychosocial, physical, and sexual abuse of women.This research aims to study is a survey research descriptive analytic. This study was a cross-sectional measurement of the independent and dependent variables is done in the same time. The population in this study were postmenopausal women aged 40-65 years who live in the Buluran Kenali Kota Jambi, the sample in this study of 77 postmenopausal women, a sample is taken by means of random sampling were analyzed using univariate and bivariate.The results found that factors affecting menopause in this study are education, income, menarche, parity, and never use kontrasepsi and does not found the effect of income, the uterus is removed, and the child-bearing age against the menopause.The study is expected to provide input for further research so that it can be beneficial to the development of obstetrics primarily to provide care in the containment procedures in women before menopause. For health centers to provide comprehensive counseling about menopause from symptoms and management.Keyword : menopause